Describing Web Services in 2005 How to make Web services consumable today. - Hinchcliffe, Dion
For years, WSDL has been synonymous with describing interoperable Web services. However, as the new venerable Web Services Description Language (WSDL) 1.1 heads towards its fifth birthday, it finds itself beset with challenges and opportunities. Currently in its second incarnation and heading for its third, WSDL has been the definitive gold standard for providing descriptions of Web services. It has especially been a smash success in terms of being the only broadly accepted format for Web service description. Moreover, it has generally done a commandable job at it, and until recently, WSDL has been without much competition.